PERAN GOOD CORPORATE GOVERNANCE TERHADAP KECURANGAN LAPORAN KEUANGAN: PERSPEKTIF FRAUD PENTAGON PADA KEMENTERIAN DAN LEMBAGA PEMERINTAH - Kurniawan, David; Reskino, Reskino (Kompartemen : Jurnal Ilmiah Akuntansi, 2023)
This study aims to examine the impact of fraud pentagon model elements on financial statement fraud and analyze the role of good corporate governance in moderating fraud pentagon model elements on fraudulent financial statements in government ministries and agencies in 2019-2021. The sample was selected based on the purposive sampling method so that 81 Ministries and Government Agencies were obtained with 243 observational data. Based on the panel data test, the results obtained show that rationalization has a significant impact on indications of fraud in financial statements. On the other hand, the factors of pressure, opportunity, competence, and arrogance cannot have a significant impact. The implementation of Good Corporate Governance is proven to moderate the effect of rationalization on the possibility of fraud in financial reports